Effects of vitamin D supplementation on ovulation and pregnancy in women with polycystic ovary syndrome: a systematic review and meta-analysis - Yang, Meina; Shen, Xiaoyang; Lu, Danhua; Peng, Jin; Zhou, Siyu; Xu, Liangzhi; Zhang, Jing (Frontiers in Endocrinology, 2023)
Objective: To evaluate the effect of vitamin D supplementation on pregnancy and ovulation in patients with polycystic ovary syndrome. Method: we searched Pubmed, Medline (via Ovid, 1974 to 2020), EMBASE (via Ovid, 1974 to 2020), Cochrane Central Register of Controlled Trials (via Ovid), Web of Science, CNKI, WangFang and the Vip database from they were established until April 2021. Two researchers independently screened articles, collected data and evaluated the quality, with Review manager 5.3 for meta-analysis. Results: Totally 20 randomized controlled studies were included, including 1961 subjects. Meta analysis showed that the pregnancy rate [RR=1.44 (1.28, 1.62), p<0.00,001], ovulation rate [RR=1.42 (1.14, 1.78), p=0.002] and matured oocytes rate [RR=1.08 (1.03, 1.13), p=0.002] of vitamin D supplementation group were significantly higher than those of the control group. The early miscarriage rate [RR=0.44 (0.30, 0.66), p＜0.00,001], androgen level [MD=-2.31 (-3.51, -1.11), p=0.0002], luteinizing hormone [MD=-1.47 (-2.57, -0.36), p=0.009], follicle stimulating hormone [MD=-0.15 (-0.24, -0.05), p=0.002], and premature delivery rate [RR=0.38, 95% CI (0.21, 0.70), p=0.002] decreased significantly. Only one article suggested that the progesterone [MD=6.52 (4.52, 8.52), p<0.05] in the vitamin D intervention group increased. There was no notable difference in the biochemical pregnancy rate [RR=0.95 (0.55, 1.63), p=0.84], gestational hypertension rate [RR=0.40, 95% CI (0.15, 1.11), p=0.08], gestational diabetes mellitus rate [RR=0.27, 95% CI (0.05, 1.39), p=0.11], fertilization rate [RR=1.05 (1.00, 1.10), p=0.04], cleavage rate [RR=1.03 (0.99, 1.06), p=0.17], high-quality embryo rate [RR=1.08 (0.98, 1.20), p=0.10], endometrial thickness [MD=0.10], 77 (-0.23, 1.77), p=0.13], estrogen level [MD=-0.34 (-1.55, 0.87), p=0.59], LH/FSH [MD=-0.14, 95% CI (-0.48, 0.20), p=1.00], anti-Mullerian hormone [MD=-0.22 (-0.65, 0.21), p=0.32], fasting blood glucose [MD=-0.52 (-1.38, 0.34), p=0.23], fasting insulin [MD=-0.02 (-0.50, 0.46), p=0.93], and HOMA-IR [MD=-0.23 (-1.77, 1.32), p=0.77]. Conclusions: in women with PCOS, vitamin D supplementation, with or without the use of ovulation induction drugs or assisted reproductive technologies, resulted in higher pregnancy and ovulation rates and lower androgen, LH, FSH and early miscarriage rates. However, no significant improvement was observed in glucose metabolism, fertilization rate or cleavage rate. Due to the limited quality of included studies, more high-quality RCTs are still needed for validation.